Maxillofacial reconstruction with prefabricated prelaminated osseous free flaps. Issue 3 (6th January 2021) - Diab, Jason; Leinkram, David; Wykes, James; Cheng, Kai; Wallace, Christine; Howes, Dale; Singh, Jasvir; Palme, Carsten; Clark, Jonathan
Abstract: Background: The prefabricated fibula flap is an advanced method of occlusal‐based reconstruction that combines placement of osseointegrated dental implants with prelamination, using a split skin graft on the fibula, weeks prior to the definitive reconstruction. This approach is resource intensive but has several advantages including eliminating the delay from reconstruction to dental rehabilitation. Methods: A retrospective cohort study of all prefabricated fibula flaps used for mandible and maxillary reconstruction from 2012 to 2020 was performed. Outcome measures were implant survival, implant utilization and functional dental rehabilitation. Results: A total of 17 prefabricated fibula flaps were performed including two analogue and 15 digital plans. There were nine maxillary and eight mandibular reconstructions, of which 11 were primary and seven were secondary. There were no free flap failures. A total of 65 implants were placed (average 3.8, median 3 implants). There was one implant failure at 6 years giving a 1.5% failure rate. There was 91% implant utilization and 94% functional dental rehabilitation. Conclusion: The prefabricated fibula flap provides outstanding dental rehabilitation in well‐selected patients. Abstract : The prefabricated fibula flap is an advanced method of occlusal‐based reconstruction that combines placement of osseointegrated dental implants with prelamination using a split skin graft on the fibula at least 6 weeks prior to the definitive reconstruction. This study provides an approach to dealing with reconstruction highlighting the advantages in terms of achieving immediate and reliable functional dental restoration.